Acidification of the electrolyte during the galvanic corrosion of AA7075: A numerical and experimental study. Issue 7 (5th February 2021) - Montoya, Rodrigo; Ruiz‐García, Allan G.; Ortiz‐Ozuna, Alma; Ramírez‐Barat, Blanca; Genesca, Juan
Abstract: The electrochemical interactions between aluminum alloy 7075 and low‐carbon steels under gelled electrolytes were studied. Such electrolytes provided the opportunity to investigate both thick and thin electrolyte systems. The electrolyte was chemically modified to visually track the acidic fronts during the anodic reaction and the subsequent hydrolysis process. Two mathematical models were validated for both thick and ultrathin electrolytes. The acidification of thick electrolytes was extended some millimeters beyond the aluminum alloy surface, whereas the acidic front was localized next to the metallic joint using ultrathin electrolytes. The combination of both numerical and experimental results allows proving (and explaining why) that the acidification process is more aggressive under dilute than under concentrated electrolytes. Graphical abstract: Finite element analysis of two different mathematical models, together with an innovative experimental setup, allows tracking acidic fronts into a gelled electrolyte during the galvanic corrosion of aluminum alloys. Thick and ultrathin electrolytes are tested to study both full immersion and atmospheric corrosive conditions on a galvanic system involving aluminum alloy 7075 and carbon steel electrodes.